Interlinkages between Socio-Economic and Demographic Characteristics and Maternal Health Service Use in Bajura District - Nepali , Bobin (Kutumbha vani, 2025)
This study has focused on how socio-demographic factors affect maternal health care access among mothers in Bajura District, Nepal, geographically challenging area where access to health services are still low. A descriptive cross-sectional design was utilized whereby after one month a total of 139 women were sampled in the District Health office through the use of a structured questionnaire. The study analyzed the relationship between age, education, occupation, ethnicity, the number of children, family type, and the distance to health facilities with the use of maternal health services, pregnancies. The findings indicated that the majority of women were young (20 34 years) with the mean age of 25.9 years and mostly were involved in agriculture (82.6%). Almost three fourths had their first pregnancy after 20, and 24.7 percent had their first pregnancy before 20. The rate of education was low and the marginalized ethnic groups were not represented. The high costs in terms of travel distance to health services and reliance on agriculture were major limiting factors to the use of services. The study conclude that the socio-economic, cultural, and geographic factors are interconnected to determine maternal health behavior. The answers to the challenges include multi-sectoral interventions that target the education of women, economic empowerment, outreach interventions to all marginalized groups, and improvements in infrastructure that will provide equitable and sustainable maternal health in remote rural Nepal.